Optimizing borderland port governance and trade efficiency in central Asian regional economic cooperation: A multidisciplinary approach to prioritizing service level agreement components - Bhatti, Omar Khalid; Irfan, Muhammad; Hanjra, Ali Raza (International Journal of Innovative Research and Scientific Studies, 2025)
Borderland Ports (BLPs) serve as the most critical nodes in global and regional trade connectivity, particularly within the Central Asian Regional Economic Cooperation (CAREC) corridor. With its growing significance, BLPs across all the 11 member countries of CAREC, consistently face governance and operational inadequacies due to high bureaucratic fragmentation, lack of inter-agency coordination and inconsistent delivery of services. Service Level Agreements (SLAs) have become an important tool for ensuring superior governance for standardizing process, procedures, accountability and operational performance at the BLPs. However, their real implementation often lacks empirical rigor, as it fails to prioritize the SLAs components based on their operational impact. The present study aims to identify the key components of Service Level Agreements at borderland ports to enhance trade, governance, port efficiency and security. Employing a four-phase hybrid methodology comprising Delphi technique, Exploratory Factor Analysis (EFA), Confirmatory Factor Analyses (CFA), and Artificial Neural Networks (ANN). The current study analyzed the responses from 704 diverse participants from 11 CAREC member states. The respondents included customs officials, logistics professionals, port authority staff, and trade experts. The findings validated the 10 key SLA components for instance confidentiality, dispute resolution, service levels and monitoring mechanism significantly affecting borderland port efficiency, inter agency coordination and infrastructure sustainability. The Study also presents a validated SLA measurement scale and a predicative model for guiding SLA formulation under complex governance conditions. By aligning SLA prioritization with the CAREC 2030 strategy for seamless trade and regional integration, the present research offers both theoretical and practical contribution for all the 11 member states. It also presents decision makers, policy experts and port authority management with empirically grounded tool for evidence-based decision making while cautioning against context-free, politically influenced SLA adoption.